An analysis of students' concept application in problem-solving of electrical circuits through inquiry-based learning - Riantoni, Cicyn; Rusdi, Rusdi; Maison, Maison; Yelianti, Upik (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study investigates students' conceptual application errors in solving electrical circuit problems in inquiry-based learning. The research involved 32 physics education students from Jambi University (24 females and 8 males) using a mixed-methods approach with an explanatory design. Students completed two multiple-choice questions with reasoning, analyzed using effect size calculation, and coded the reasoning responses to assess conceptual application. The results revealed an effect size of 0.7, indicating a moderate impact of inquiry-based learning on conceptual application in problem-solving. Further analysis showed that correct answers did not always reflect accurate conceptual understanding. For example, in the first question, 62.5% of students selected option D, but not all provided conceptually correct reasoning. In the second question, only 37.5% answered correctly. These findings suggest the need for additional support, such as reflective sessions and scaffolding, to enhance students' conceptual understanding and critical thinking skills in problem-solving tasks.